2021
DOI: 10.3390/pharmaceutics14010037
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Hydrogel Containing Viscum album Extract for Topic and Transdermal Use: Development, Stability and Cytotoxicity Activity

Abstract: Viscum album L. (Santalaceae), also known as European mistletoe, is a semi-parasitic plant that grows on different host trees. Our group recently demonstrated the antitumoral activity of ethanolic V. album extracts in vitro, depending on the dose and the host tree, V. album ssp abietis from Abies alba being the most active extract. The goal of this work focused on the development of a new topical formulation containing V. album extracts, evaluation of in vitro toxicity and ex vivo skin permeation assays. The P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 65 publications
(107 reference statements)
1
18
0
Order By: Relevance
“…Therefore, our study identified the total pool of polyphenols accumulated in the skin. Many authors confirm the accumulation of polyphenols in of the skin (Martimestres et al, 2007;Alonso et al, 2014Alonso et al, , 2015Batista et al, 2021). The difference between the intensity of C-H bonds of the skin treated of the HEas and control sample was observed.…”
Section: Strain Of Bacteriamentioning
confidence: 74%
See 2 more Smart Citations
“…Therefore, our study identified the total pool of polyphenols accumulated in the skin. Many authors confirm the accumulation of polyphenols in of the skin (Martimestres et al, 2007;Alonso et al, 2014Alonso et al, , 2015Batista et al, 2021). The difference between the intensity of C-H bonds of the skin treated of the HEas and control sample was observed.…”
Section: Strain Of Bacteriamentioning
confidence: 74%
“…The composition of the formulation is a significant factor. The results of our research on the penetration of phenolic acids was likely to be exerted by the moisturizing ingredient of the preparation, such as propylene glycol, which enhance membrane permeability by acting as an absorption promoter (Ratz-Łyko et al, 2015;Batista et al, 2021). Greater delivery of the active substance to the skin increases the effect of cosmetic and dermatological preparations.…”
Section: Strain Of Bacteriamentioning
confidence: 85%
See 1 more Smart Citation
“…Hydrogels also appear to be an excellent approach for controlled drug delivery. Along this line, Batista et al presented a new thermosensitive hydrogel topical formulation containing Viscum album (mistletoe) extracts [ 28 ]. An additional publication explored the incorporation of cyclodextrin during resveratrol extraction.…”
mentioning
confidence: 99%
“…Viscum album L. is a plant species, which clinical importance has been registered either as monotherapy or adjunct therapy for patients with cancer 1 , 2 . Itʼs well known the use of different extracts in the V. album preparations that influence the wide diversity of metabolites detected in these pharmaceutical preparations 3 , 4 , 5 . The objective of this study was to evaluate the physico-chemical and antitumoral in vitro effect of a hydrogel containing ethanolic dry extract of V. album (host tree Abies alba).…”
mentioning
confidence: 99%